The Influence of the Project-Based Learning (PjBL) Model Based on Differentiated Strategies on Students Spiritual Intelligence - Rizka Arista Sofiyana; Eges Triwahyuni; Abdul Muis (Postgraduate, University of Mataram, 2024)
This research was motivated by the inadequate spiritual intelligence of students. This is due to demands and pressure to achieve certain academic targets, thereby ignoring spiritual intelligence; Limited time and resources covering all aspects of student development, so that spiritual intelligence is not a top priority; and shifts in societal and cultural values ​​as a result of modernization. The purpose of the curriculum is to provide guidance for teachers in conveying learning material systematically to students. In the Independent Curriculum which is currently being implemented in many schools, the implementation of learning becomes more flexible. The aim of this research is to describe the influence of the PjBL Model based on differentiated strategies on students' spiritual intelligence. The research method used was Quasi Experiment with a Nonequivalent Pretest-Posttest Only Control Group Design. The research instrument used was a spiritual intelligence questionnaire. The results of the research show that the spiritual intelligence of students taught using the PjBL Model based on differentiated strategies is higher than those taught using conventional learning, where the average spiritual intelligence value of experimental group students is 83.5 and the average spiritual intelligence value control group students was 77.87. Thus, it can be concluded that the PjBL Model based on differentiated strategies has a significant effect on students' spiritual intelligence.